Motorcycle Financing Transactions at PT Bank Sumut Syariah Panyabungan Sub-Branch: Islamic Law Perspective - Siti Kholijah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The main principle of islamic life is monotheism of Allah, namely an awareness that human life is a mandate from Allah. The word muamalat is the only word that literally means "doing each other" or reciprocity. Muamalah is etymologically the same and meaningful with almufa'alah, namely doing each other. The research objective is to analyze motorcycle financing transactions at PT Bank Sumut Syariah Panyabungan Sub-Branch as islamic law perspective. This research includes field research. The method used in this research is qualitative method. Sources of data in this study are primary and secondary data. The writing method uses the inductive method. The results showed that motorcycle financing transactions at PT Bank Sumut Syariah Panyabungan Sub-Branch based on a murabahah contract, the profit is immediately known. The benefits of murabaha are immediately known at the beginning when the murabaha transaction is agreed upon. Customers are given convenience in paying off motorcycle financing, so that customers feel lucky. Motorcycle financing transactions at PT Bank Sumut Syariah Panyabungan Sub-Branch is in accordance with islamic law, because this murabahah contract is a sale and purchase agreement of sharia goods, meaning that it is in accordance with islamic law. The profits obtained are not based on usury, but a profit-sharing system between the customer and the bank.